Prevalensi Defisiensi Penglihatan Warna Anak Usia Sekolah Dasar Di Sekolah-X Tanjung Duren Selatan 05 - Sinaga, Natasya Advelin; Silaen, Desi Hartati; Goenawan, Kristian (Universitas Kristen Krida Wacana, 2024)
Color vision deficiency is the inability of the eye to distinguish colors, this can occur both congenitally and acquired. Color vision deficiency can affect a person's quality of life performance and the selection of advanced study programs in children. This study aims to determine the prevalence and characteristics of color vision deficiency in detail in elementary school-age children. This study used a total sampling technique with a cross sectional method with 366 respondents. Data collection was carried out from September to October. In this study, 5.2% (10 people) of respondents experienced color vision deficiency. As many as 2.2% (8 people) of respondents had partial color vision deficiency and 0.5% (2 people) of respondents had color blindness (monochromat). Of the 195 male respondents, 4.6% of them suffered from color vision deficiency while of the 171 female respondents, 0.6% of them suffered from color vision deficiency. Color vision is related to cone cell photoreceptors. Each type of cone cell plays a role in color vision. The prevalence of students with color vision deficiency is 2.7%. In this study it was found that students had partial and total color vision deficiency (monochromat). The most common type of red-green color vision deficiency. The highest prevalence is in male students. It is recommended to the government and schools to carry out a complete eye examination including a color vision examination so that it can support the learning process and the selection of advanced study programs according to the child's condition.